I know that a way of proving Poincare lemma is to use the homotopy invariance and contractibility of the Euclidean space. Is there is a way of doing it directly (without using the contractibility of $\mathbb{R}^n$)? What was the first proof of this statement ? I wish to know all the different ways of proving this lemma. Please provide references. Thanks !

  • 2
    $\begingroup$ I know a proof which uses a linear operator $t$ on smooth forms s.t. $dt+td=id$: so, if $\omega$ is closed, then $dt\omega=\omega$ and $\theta:=t\omega$ gives the solution (i.e. proves that $\omega$ is exact). Would you like it in an answer? $\endgroup$
    – Avitus
    Nov 10, 2013 at 21:03
  • 1
    $\begingroup$ @Avitus May be you mean $dt+td=i$. I think it would definitely be helpful if you could outline this or give a reference. $\endgroup$
    – user90041
    Nov 11, 2013 at 2:06
  • $\begingroup$ @Avitus The original reason why I asked this question was that if I expand the given form as linear combination of wedge product of the coordinate 1-forms, I can see that Poincare lemma is a statement about existence of a solution to a set of partial differential equations. If there is another proof of this lemma using the theory of PDEs, I would like to learn that as well. $\endgroup$
    – user90041
    Nov 11, 2013 at 2:13
  • 3
    $\begingroup$ According to Dieudonné's book on the history of algebraic and differential topology, it appears in Volterra, Opere mathematiche vol. I pp. 407-422 for the first time, but "in a different language" (whatever that's ought to mean) and the next appearance is E. Cartan's book Leçons sur le Invariants Intégraux 1922. I don't know these books, but I expect that at least the latter is readable and can easily be turned into a rigorous proof in modern language. $\endgroup$
    – Ben
    Nov 11, 2013 at 22:52

3 Answers 3


We want to show that on $\mathbb R^n$, all closed forms of degree $p\geq 1$ are exact. To do so we construct a linear operator

$$\alpha:\Omega^p(\mathbb R^n) \rightarrow \Omega^{p-1}(\mathbb R^n) $$

s.t. $$d\alpha+\alpha d=1.$$

Let $\omega$ be a closed $p$-form. Then, for any $x\in\mathbb R^n$ we define

$$(\alpha \omega)(x):=\int_0^1 t^{p-1}i_x\omega(tx)dt, $$

where $i_x$ is the interior product operator. Then (by Cartan's magic formula)

$$\begin{aligned} ((d\alpha + \alpha d)\omega)(x) & = \int_0^1 t^p\mathcal L_x\omega(tx)dt \\ & =(\text{use chain rule and pull-back definition of Lie derivative}) \\ & = \int_0^1\frac{d}{dt}(t^p\omega(tx))dt=\omega(x) \end{aligned} $$

and we are done. The diff. form $\theta:=\alpha(\omega)$ is the exact form we need.

edit: For the chain rule step one wants to consider the pull-back $M_t^* \omega$ where $M_t : \mathbb R^n \to \mathbb R^n$ is scalar multiplication by $t$. i.e. $t^p \omega(tx) = M_t^* \omega (x)$.

  • $\begingroup$ I am having trouble following your last chain of equalities. I do not quite see how you "use chain rule and pull-back definition of Lie derivative," nor how you get $t^p$ instead of $t^{p-1}$ in the first equality. $\endgroup$
    – Greyson
    Feb 4, 2018 at 17:41

We describe a linear functional $\alpha : \Omega^p \mathbb R^n \to \Omega^{p-1} \mathbb R^n$. The space alternating $p$-linear functions on $\mathbb R^n$ has dimension $n \choose p$, and you can write the basis as $dx_{i_1} \wedge dx_{i_2} \wedge \cdots \wedge dx_{i_p}$ where $1 \leq i_1 < i_2 < \cdots < i_p \leq n$. If $I = (i_1, i_2, \cdots, i_p)$ is such a multi-index let $dx_I = dx_{i_1} \wedge dx_{i_2} \wedge \cdots \wedge dx_{i_p}$. Let $I_1$ be the collection of multi-indices with $i_1=1$ and let $I_2$ be the collection of multi-indices with $i_1 > 1$.

Given a $p$-form $f dx_I$ with $f: \mathbb R^n \to \mathbb R$ we define $\alpha$ linearly, by $\alpha (f dx_I) = 0$ if $I \in I_2$. $\alpha (fdx_I) = \left(\int_0^{x_1} f dx_1\right) dx_{i_2} \wedge \cdots \wedge dx_{i_p}$ if $I \in I_1$. You can think of $\alpha$ is a type of `total contraction' of the form in the coordinate $x_1$-direction.

It's fairly direct to check that $$ d(\alpha(\omega)) + \alpha(d \omega) = \omega - \pi^*(i^* \omega)$$ for every $p$-form $\omega$. Here $i : \mathbb R^{n-1} \to \mathbb R^n$ is the inclusion $i(x_2,\cdots,x_n) = (0,x_2,\cdots,x_n)$ and $\pi : \mathbb R^n \to \mathbb R^{n-1}$ is projection $\pi(x_1,x_2,\cdots,x_n) = (x_2,\cdots,x_n)$.

So this is a less technically-sophisticated argument than Avitus's but it might be a little simpler to follow conceptually. In the end you reduce showing a closed $p$-form on $\mathbb R^n$ is exact to solving the problem for one smaller $n$. Dimension $p=n$ is the base case, where the above formula starts the induction.

  • $\begingroup$ This looks very similar to Bott&Tu's proof! $\endgroup$ May 22, 2016 at 5:13
  • 2
    $\begingroup$ Perhaps because Tu and I are both Edmontonians. $\endgroup$ Jul 2, 2019 at 19:18

The above calculation in more detail. Define $h_k:\Omega^p(\mathbb{R}^n)\rightarrow \Omega^{p-1}(\mathbb{R}^n)$ by, \begin{eqnarray} h_k(\omega)(x)=\int_0^1t^{p-1}i_X\omega(tx)dt \end{eqnarray} where $X=\sum_ix^i\partial_i$, this generates the one parameter group of diffeomorphisms $\Phi_s:x^i\mapsto e^sx^i=:y^i$. To see this note that $X^i(t)=\frac{dx^i(t)}{dt}=x^i(t)$, hence we solve this ODE to find the stated solution. Now, \begin{eqnarray} ((h_{k+1}\circ d_k+d_{k-1}\circ h_k)\omega)(x)&=&\int_0^1t^{p-1}\Big(d(i_X\omega)+i_X(d\omega)\Big)(tx)dt\\ &=&\int_0^1t^{p-1}(\mathcal{L}_X\omega)(tx)dt \end{eqnarray} Then from the definition of the Lie derivative in terms of the pullback, \begin{eqnarray} (\mathcal{L}_X\omega)_x=\Big(\frac{d}{ds}\Big|_{s=0}(\Phi_s)^*\omega\Big)_x \end{eqnarray} Now we can compute the pullback explicitly, \begin{eqnarray} [((\Phi_s)^*\omega)_x]_{k_1...k_p}=\frac{\partial y^{i_1}}{\partial x^{k_1}}...\frac{\partial y^{i_p}}{\partial x^{k_p}}[\omega_{\Phi_s(x)}]_{i_1...i_p}=e^{ps}[\omega_{e^sx}]_{k_1...k_p} \end{eqnarray} Due to linearity we can restrict to the simple case where $\omega(x)=f(x)dx^I$. Therefore, \begin{eqnarray} (\mathcal{L}_X\omega)_x=\Big(\frac{d}{ds}\Big|_{s=0}(\Phi_s)^*\omega\Big)_x=p\omega_x+x^i\frac{\partial f}{\partial x^i}(x)dx^I \end{eqnarray} Therefore, \begin{eqnarray} t^{p-1}(\mathcal{L}_X\omega)_{tx}&=&t^{p-1}\Big(p\omega_{tx}+tx^i\frac{\partial f}{\partial x^i}(tx)dx^I\Big)\\ &=&\frac{d}{dt}\Big(t^pf(tx)dx^I\Big)=\frac{d}{dt}(t^p\omega(tx)) \end{eqnarray} Hence, \begin{eqnarray} ((h_{k+1}\circ d_k+d_{k-1}\circ h_k)\omega)(x)=t^p\omega(tx)|_{t=0}^1=\omega(x) \end{eqnarray} Therefore since $\omega$ is closed, $d\omega=0$ so $\mathcal{L}_X\omega=d(i_X\omega)$ and hence $d_{k-1}h_k\omega=\omega$, i.e. $\omega$ is exact.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.